The Role of Inquiry Based Learning in Science Learning: A Systematic Review of Literature - Ainun Nadira; Insih Wilujeng; Heru Kuswanto; Nisya Indriyanti Irawan; Malik Wira Gustama (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine the role of Inquiry-Based Learning (IBL) in improving the quality of science learning through a systematic literature review. The methodology followed the PRISMA framework, analyzing 17 reputable scientific articles retrieved from the Scopus database between 2018 and 2024. The results of the study indicate that IBL has a significant positive impact on science learning, particularly in enhancing students’ conceptual understanding, scientific process skills, and critical thinking abilities. Additionally, IBL contributes to increasing students’ motivation and positive attitudes toward science through active engagement in the learning process. Further discussion reveals that the success of IBL implementation is influenced by various factors, such as teacher readiness, availability of facilities, and learning time management. Nevertheless, IBL remains an effective approach in supporting student-centered science learning. Overall, this study concludes that IBL has great potential in improving the quality of science learning, but requires appropriate support and implementation strategies to be applied optimally